Alternative scapular stabilization exercises to target strength, endurance and function of shoulders in tetraplegia: A prospective non-controlled intervention study. (2nd January 2019) - Lins, Carolina; Castro, Alex; Medina, Giovanna I.S.; Azevedo, Eliza R.F.B.M.; Donato, Bruno S.; Chagas, Marina S.S.; Tancredo, Janaína Roland; Vargas de Almeida, Letícia; Cliquet, Alberto
Abstract : Objective: Scapular stabilization exercises (SSE) are well-established for the able-bodies. The aim of the current study is to access the potential benefits of SSE on isometric internal and external rotator strength, endurance and function of the shoulder in persons with tetraplegia, throughout a 12-week exercise program consisting of five resisted movements with elastic bands. Design: Prospective non-controlled intervention study. Setting/Participants/Interventions: A convenience sample of 17 subjects (age, 40.0±10.0 years old) with SCI was recruited from the University Hospital at the State University of Campinas (UNICAMP) from March 2015 to February 2016. They performed 5-resisted-SSE for 12 weeks, using Thera-band® elastic bands. Four evaluations were required: Baseline1, Baseline2, 6W and 12W. Outcome measures: The dependent variables were isometric internal and external rotation strength, flexion and abduction endurance and the Disabilities of the Arm, Shoulder and Hand (DASH) score. Results: Isometric external rotation strength and flexion endurance increased after SSE and were classified as "clinically relevant" using minimal importance difference (MID). Abduction endurance increased but it was classified as "not clinically relevant". DASH score reported no significant differences but it was classified as "potentially clinically relevant". Correlations were observed among time since injury and endurance improvements. Conclusion: This study demonstrated that specific training of the scapula muscles shows a benefit for shoulder strength, endurance and function of the shoulder in subjects with tetraplegia and should be part of the rehabilitation program. Besides, the SSE can be performed by subjects with tetraplegia themselves on a regular basis.